2014
DOI: 10.5051/jpis.2014.44.5.216
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of autogenous tooth bone graft and synthetic bone graft materials used for bone resorption around implants after crestal approach sinus lifting: a retrospective study

Abstract: PurposeThis retrospective study compares the amount of bone resorption around implants between an autogenous tooth bone graft (AutoBT) and a synthetic bone graft after a bone-added crestally approached sinus lift with simultaneous implant placements.MethodsIn all, 37 patients participated in this study. Seventeen patients were grouped as group I and underwent an AutoBT-added sinus lift using the crestal approach. The remaining 20 patients were grouped as group II and underwent synthetic bone grafting. Both gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 20 publications
2
60
0
2
Order By: Relevance
“…AutoBT with composites of 30 % β-TCP and 70 % HAp in human sinus, an average bone resorption was 0.76 mm with AutoBT powders while 0.53 mm with osteon composites 8) . Lastly, when comparing AutoBT powders with a bovine-derived inorganic material (Bio-Oss) in human sinus, they showed similar healing pattern, excellent graft volume maintenance, and active new bone formation while the trabecular and osteoid in the AutoBT group were thicker than those in the Bio-Oss group 9) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AutoBT with composites of 30 % β-TCP and 70 % HAp in human sinus, an average bone resorption was 0.76 mm with AutoBT powders while 0.53 mm with osteon composites 8) . Lastly, when comparing AutoBT powders with a bovine-derived inorganic material (Bio-Oss) in human sinus, they showed similar healing pattern, excellent graft volume maintenance, and active new bone formation while the trabecular and osteoid in the AutoBT group were thicker than those in the Bio-Oss group 9) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been found to be an excellent biocompatible material with osteoinductive and osteoconductive potential by bio-recycling of the tooth, which has been discarded traditionally after the extraction 1,6,7) . Also, clinical reports were already published that AutoBT by itself had great ability for new bone formation and remodeling, comparing to another graft materials in sinus 8,9) . Several base materials such as hydroxypropylmethyl cellulose (HPMC) and hyaluronc acid in order to increase the viscosity of bone graft substitute or to promote cellular activities for bone regeneration have been reported and confirmed its safety and better performance 10) .…”
Section: Introductionmentioning
confidence: 99%
“…7 A study conducted by Kim YK et al concluded that auto block type tooth bone graft can be considered a good alternative bone graft to a synthetic bone graft in a bone-added sinus lift, when extraction is necessary prior to the surgery. 8 Murata M et al first confirmed the osteo-inductive property of human demineralized dentin matrix (DDM) histologically. The DDM induced bone and cartilage independently 9 .…”
Section: Discussionmentioning
confidence: 99%
“…23 Highly mineralized materials cannot be easily resorbed, thus limiting or even hampering their osteointegration and bone formation in vivo. 13,24,25 In this light, demineralization was found to be very promising for overcoming such drawbacks through the improvement of the in vivo performance of tooth derivatives. 26 In this study we evaluated the effects of the demineralization process on morphology and topography as well as on the chemical compositions of tooth particles by means of SEM/EDS analyses.…”
Section: Demineralization Effects On Bt Surface Morphology and Chemicmentioning
confidence: 99%